Rapid development of HPV-mediated oropharyngeal squamous cell carcinoma in the setting of immune suppression following autologous stem cell transplantation for Hodgkin lymphoma - Joo Y. Song; Ellie Maghami; Huiqing Wu; Young S. Kim; Dennis D. Weisenburger; Alexandra Levine; Auayporn Nademanee (Elsevier, 2017)
The patient is a 61-year-old male with a diagnosis of relapse classical Hodgkin lymphoma, treated with ABVD, ICE, and achieved remission. He underwent autologous stem cell transplantation and 3 months later found to have a PET-positive neck node concerning for relapsed disease of Hodgkin lymphoma. Biopsy proved the lesion was HPV-associated squamous cell carcinoma and not relapse Hodgkin disease. Iatrogenic immunosuppression such as bone marrow transplantation can cause substantial increase risk for viral-associated tumors and therefore tissue biopsies are necessary to make that distinction to avoid inappropriate treatment. Keywords: Hodgkin lymphoma, HPV, Squamous cell carcinoma, Transplantation